Automation of measurement of objects geometrical parameters - Rybalka, A.; Megel, Y.; Kalimanova, I.; Kovalenko, S.; Kovalenko, S. (Технический университет - София - Технологии, 2017)
The issues of automation of measurement of the basic physical and geometrical parameters of biological object and possibility to obtain quantitative characteristics by optical methods are considered in the article. The prospects of the method of pattern recognition to distinguish the contour of the object in order to increase descriptiveness and precision measurement are shown.
Keywords: biological object; pattern recognition; optical system; measurement